Telecentres Go Where Mobile Phones Fear to Tread: Evidence from India. (April 2014) - Ray, Rupamanjari Sinha; Prasad, Rohit
As broadband becomes an integral part of universal service schemes in emerging economies, the lines between universal access to telephony and universal access to computing are blurring. This article focuses on the social inclusiveness of publicly funded telecentres in India. In contrast to the previous literature, it does not test their inclusiveness in absolute terms, but relative to the inclusiveness of mobile phones. Data from telecentres set up in two states in India under the National Common Service Centre Scheme shows that mobile and telecentre adoption is driven by different factors. This suggests that telecentre adoption could take precedence over mobile adoption in certain socio-economic categories like females and agriculturists. We show that this is indeed true among females where telecentres are substitutes for mobiles. Among males the two media behave as complements. This suggests that telecentres and mobiles must play complementary roles in bringing connectivity to rural areas. The optimism on telecentre performance with respect to women has to be tempered with a sober reflection on commercial viability.